Radiation emission from video display terminals - Paimin, Razis (Universiti Malaysia Sarawak (UNIMAS), 2010)
Electromagnetism is an example of nature force, besides than nuclear energy and gravity where it can be found almost everywhere. This energy is used in many ways but people still lack the full understanding of its fundamental properties. A lot of creations based on electromagnetism ranging from everyday home to offices appliances are important and advantageous. For examples, the application of computers and the accompanying use of video display terminals (VDTs) are changing the living and working lifestyles. Manufacturer and individual users of computers are certainly aware of the benefits generated from this technology but only few users are aware of the real risks derived from the exposure to the electromagnetic radiation emissions from VDTs. Thus, the research is done to study the possible adverse health effect that may occur from the radiation. Experiments are conducted to measure the temperature of the body part that exposed to the radiation. The temperature is measured using thermal imaging camera in certain amount of time and calculated using appropriate equation to measure the specific absorption rate (SAR). The results of the experiment will demonstrate the amounts of radiation that expose to the human body and in longer period, it may affect human health.